RYBP predicts survival of patients with non-small cell lung cancer and regulates tumor cell growth and the response to chemotherapy. Issue 2 (28th December 2015) - Voruganti, Sukesh; Xu, Fangxiu; Qin, Jiang-Jiang; Guo, Yan; Sarkar, Sushanta; Gao, Ming; Zheng, Zhijie; Wang, Ming-Hai; Zhou, Jianwei; Qian, Biyun; Zhang, Ruiwen; Wang, Wei
Highlights: Both RYBP mRNA and protein expression levels are downregulated in NSCLC tissues. The low level of RYBP predicts poor patient survival in NSCLC. RYBP overexpression inhibits cell viability and induces apoptosis in NSCLC cells. One of the main mechanisms of RYBP-mediated cell growth inhibition is apoptosis. Successful AdRYBP infection inhibits NSCLC tumor xenograft growth. Chemotherapeutic agents induce the expression of RYBP. RYBP sensitizes NSCLC cells to conventional chemotherapy both in vitro and in vivo . Abstract: Ring1 and YY1 binding protein (RYBP) is a member of the Polycomb group (PcG) proteins and regulates cell growth through both PcG-dependent and -independent mechanisms. Our initial study indicated that RYBP is down-regulated in human non-small cell lung cancer (NSCLC) tissues. The present study determined the molecular role of RYBP in the development of NSCLC. We systemically investigated the association between the RYBP expression and the survival of patients with NSCLC. We also carried out in vitro and in vivo studies to explore the molecular basis for the tumor suppressor role of RYBP in NSCLC. Our clinical results demonstrated that the RYBP mRNA and protein expressions were significantly down-regulated in NSCLC and significantly linked to the poor prognosis in NSCLC patients. The enforced expression of RYBP inhibited cell survival, induced apoptosis, and increased chemosensitivity in NSCLC cells; knockdown of RYBP showed the opposite effects. Moreover, adenoviral delivery of RYBP sensitized the NSCLC cells to chemotherapy in vivo . In addition, RYBP expression was induced by paclitaxel, the first-line chemotherapeutic agent for NSCLC. Our results reveal that RYBP inhibits the aggressiveness of NSCLC cells and downregulation of RYBP is associated with poor prognosis, suggesting that RYBP could be developed as a biomarker and a novel target for therapy in patients with lung cancer.